2007
DOI: 10.1007/s00340-007-2596-8
|View full text |Cite
|
Sign up to set email alerts
|

Construct a polarizing beam splitter by an anisotropic metamaterial slab

Abstract: The propagation of electromagnetic waves in the anisotropic medium with a single-sheeted hyperboloid dispersion relation is investigated. It is found that in such an anisotropic medium Eand H-polarized waves have the same dispersion relation, while E-and H-polarized waves exhibit opposite amphoteric refraction characteristics. E-(or H-) polarized waves are positively refracted whereas H-(or E-) polarized waves are negatively refracted at the interface associated with the anisotropic medium. By suitably using t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The backward surface wave can be excited even if the constants in the relative permittivity and permeability tensors of anisotropic metamaterial are not all negative. As theoretical investigation in reference [15], a compact and very efficient beam splitter based on large birefringence can be only made of AMM slab to route wave, if one polarized wave is positively refracted (v gx > 0) whereas the other is negatively refracted (v gx < 0). The AMM slab can be realized with ring and rod.…”
Section: Never Cutoff Media Slabs Casementioning
confidence: 99%
See 1 more Smart Citation
“…The backward surface wave can be excited even if the constants in the relative permittivity and permeability tensors of anisotropic metamaterial are not all negative. As theoretical investigation in reference [15], a compact and very efficient beam splitter based on large birefringence can be only made of AMM slab to route wave, if one polarized wave is positively refracted (v gx > 0) whereas the other is negatively refracted (v gx < 0). The AMM slab can be realized with ring and rod.…”
Section: Never Cutoff Media Slabs Casementioning
confidence: 99%
“…Some propagation characteristics of electromagnetic (EM) waves associated with AMM have been analytically discussed. Such as negative GoosHänchen shift [11,12], anomalous reflection, total reflection [13], and total transmission [14] at the interfaces between isotropic regular media and AMM et al Anisotropic metamaterials have potential applications in polarizing beam splitter [15], a band separating device [16], solidstate spectroscopy, and Omnidirectional linear polarizer et al…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the negative refraction has also been demonstrated experimentally at the interface associated with a wedge composed of anisotropic metamaterial cut along nonprincipal axes [17], indicating that certain classes of anisotropic media have identical refractive properties as isotropic negative index materials [18]. Such materials can be readily constructed using different resonant inclusions such as SRRs and rods to demonstrate negative refraction, and they have potential applications in imaging, polarizing beam splitter, and wave guiding [19][20][21].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the electromagnetic characteristics of anisotropic metamaterial, in which the components of the permittivity and permeability tensors are not all of the same sign, have been discussed theoretically and experimentally in many literatures [11][12][13][14][15][16][17][18][19][20][21][22][23]. Lindell et al have demonstrated that the occurrence of negative refraction at the interface associated with uniaxially anisotropic media requires only one tensor component with a negative value [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the propagations and characteristics of metamaterial are significantly different from those of isotropic materials [3][4][5][6][7][8][9][10][11][12][13][14][15]. Metamaterial has many unusual properties and may lead to important applications, such as absorber [16], wave splitter [17], and subwavelength rectangular cavity [18].…”
Section: Introductionmentioning
confidence: 99%